Choroid plexus carcinoma: Report of two cases - Singh Avninder; Vermani Sarvjot; Shruti Sharma (Wolters Kluwer Medknow Publications, 2009)
Choroid plexus carcinomas (CPCs) are rare malignant counterparts of choroid plexus papilloma which occur in infants and children with a predilection for the posterior fossa and have a poor prognosis. We report two cases of CPC diagnosed in a 5-year-old boy and a 12-year-old boy and discuss the clinicopathologic features.